2011
DOI: 10.5539/ijb.v3n2p162
|View full text |Cite
|
Sign up to set email alerts
|

Flammulina Velutipes (Curt.: Fr.) Singer: An Edible Mushroom in Northern Forest of Iran and its Antagonistic Activity Against Selected Plant Pathogenic Fungi

Abstract: Flammulina velutipes is known as edible and medicinal mushroom. The fungus grow on living trees of Zelkova carpinifolia and dead trees of Diospyros lotus (Stand and fallen) in Behshar forest area. These plants were found as new hosts for F. velutipes. In vitro antagonistic activity of this mushroom against Bipolaris sorokiniana, Ophiostoma ulmi, Pestalotiopsis funerea, Fusarium culmurum, and Fusarium oxysporum was evaluated on MEA as dual culture. Colonies of the fungus were white farinaceous and powdery on ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…Reshetnikov (1991) listed as many as 151 species of Agaricales and 73 species of aphyllophoroid basidiomycetes known to develop arthroconidia. Among them are the species, potentially similar to our sample: Pleurotus cystidiosus Miller 1969 (Buchalo 1988) and mentioned above Flammulina velutipes (Reshetnikov 1991;Borhani et al 2011); and many aphilophoroid fungi, including the earlier mentioned species of the genus Amylostereum Boidin 1958.…”
Section: Discussionsupporting
confidence: 61%
“…Reshetnikov (1991) listed as many as 151 species of Agaricales and 73 species of aphyllophoroid basidiomycetes known to develop arthroconidia. Among them are the species, potentially similar to our sample: Pleurotus cystidiosus Miller 1969 (Buchalo 1988) and mentioned above Flammulina velutipes (Reshetnikov 1991;Borhani et al 2011); and many aphilophoroid fungi, including the earlier mentioned species of the genus Amylostereum Boidin 1958.…”
Section: Discussionsupporting
confidence: 61%
“…Similarly, the methanol extract of Macedonian wild F. velutipes fruiting body was demonstrated to show antibacterial activity against both Gram-positive and Gram-negative bacteria, including B. subtilis, Bacillus pumilus, S. aureus , and Pseudomonas aeruginosa (Nedelkoska et al, 2013). Besides that, the antagonistic activity of F. velutipes against plant pathogenic fungi was also examined by evaluating the competitive interactions of the mushroom and the pathogens in a dual culture in vitro experiment (Borhani et al, 2011). The study showed that after an initial deadlock, F. velutipes was able to completely replace Ophiostoma ulmi by F. velutipes .…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…The study showed that after an initial deadlock, F. velutipes was able to completely replace Ophiostoma ulmi by F. velutipes . F. velutipes also partially replaced the other three plant pathogenic fungi tested namely Fusarium oxysporum, Pestalotiopsis funerea and Fusarium culmurum LM2091 (Borhani et al, 2011). Recently, a study demonstrated that the extract from F. velutipes exhibited inhibitory activity toward the adhesion of pathogenic fungi ( Sporothrix schenckii and Candida albicans ) to epithelial cells (L929 cell line) (Kashina et al, 2016).…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Представители F. velutipes, как и большинство съедобных грибов, способствуют развитию противовоспалительного эффекта при хронических воспалительных процессах у млекопитающих и человека [12]. Экстракты из F. velutipes способны оказывать иммуномодулирующее, противоопухолевое, антиоксидантное, тромболитическое, фибринолитическое, гипотензивное, антибактериальное, антифунгицидное, противирусное действие и характеризуется наличием определенного влияния на митотическую активность клеток [13][14][15][16].…”
Section: в п о м о щ ь п р а к т и ч е с к о м у в р а ч уunclassified